2015
DOI: 10.1016/j.envpol.2015.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Using foliar and forest floor mercury concentrations to assess spatial patterns of mercury deposition

Abstract: We evaluated spatial patterns of mercury (Hg) deposition through analysis of foliage and forest floor samples from 45 sites across Adirondack Park, NY. Species-specific differences in foliar Hg were evident with the lowest concentrations found in first-year conifer needles and highest concentrations found in black cherry (Prunus serotina). For foliage and forest floor samples, latitude and longitude were negatively correlated with Hg concentrations, likely because of proximity to emission sources, while elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 46 publications
(69 reference statements)
2
28
1
Order By: Relevance
“…and a series of papers list foliage concentrations of various tree species between 15 and 59 ng g À1 (St. Louis et al, 2001;Grigal et al, 2000;Rasmussen, 1991;Melieres et al, 2003;Gong et al, 2014;Blackwell and Driscoll, 2015). Combining with on our previous study in remote and suburb areas in China Zhou et al, 2013Zhou et al, , 2015b, it is interesting to find that litter or litterfall mercury concentrations were much higher than that in North America and Europe as presentation above.…”
Section: Mercury In Atmospherementioning
confidence: 66%
“…and a series of papers list foliage concentrations of various tree species between 15 and 59 ng g À1 (St. Louis et al, 2001;Grigal et al, 2000;Rasmussen, 1991;Melieres et al, 2003;Gong et al, 2014;Blackwell and Driscoll, 2015). Combining with on our previous study in remote and suburb areas in China Zhou et al, 2013Zhou et al, , 2015b, it is interesting to find that litter or litterfall mercury concentrations were much higher than that in North America and Europe as presentation above.…”
Section: Mercury In Atmospherementioning
confidence: 66%
“…[] showed that scavengeable atmospheric Hg increases with elevation in Nevada and California. Furthermore, multiple studies found increasing soil Hg concentration with elevation in montane forests and proposed that higher Hg(II) deposition via throughfall and cloudwater at higher elevation could contribute to the altitudinal Hg enrichment [ Zhang et al ., ; Blackwell and Driscoll , ; a]. It is possible that the elevation trend in our study is codetermined by the effects of precipitation and forest type.…”
Section: Resultsmentioning
confidence: 87%
“…Non-precipitation Hg wet deposition, e.g., cloud, fog, dew, and frost, could account for a notable proportion of the total wet deposition in montane, coastal, arid, and semi-arid areas Sheu and Lin, 2011;Stankwitz et al, 2012;Blackwell and Driscoll, 2015b). Quantifying Hg in cloud or fog helps better understand the impact of long-range transport and local sources on global Hg cycling .…”
Section: Measurements Of Hg Wet Deposition Through Cloud Fog Dew Amentioning
confidence: 99%
“…Non-precipitation Hg wet deposition simulation has never been considered in CTMs, but performed in some individual studies with Hg concentration data for cloud, fog, dew, or frost samples (Ritchie et al, 2006;Converse et al, 2014;Blackwell and Driscoll, 2015b). Non-precipitation deposition depth can be estimated using resistance models, analytical models, or sophisticated atmosphere-soil-vegetation models.…”
Section: Model For Non-precipitation Hg Wet Depositionmentioning
confidence: 99%
See 1 more Smart Citation